-4(r+3)=-70

Simple and best practice solution for -4(r+3)=-70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(r+3)=-70 equation:


Simplifying
-4(r + 3) = -70

Reorder the terms:
-4(3 + r) = -70
(3 * -4 + r * -4) = -70
(-12 + -4r) = -70

Solving
-12 + -4r = -70

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -4r = -70 + 12

Combine like terms: -12 + 12 = 0
0 + -4r = -70 + 12
-4r = -70 + 12

Combine like terms: -70 + 12 = -58
-4r = -58

Divide each side by '-4'.
r = 14.5

Simplifying
r = 14.5

See similar equations:

| 3x+5+3x+5+x+x=66 | | 2x-6x+8x-9x= | | (2x+3)(x+5)= | | m^2-28m+25=0 | | 6k-k=27-4 | | 43(x-172)=86 | | 5x^2+34+24=0 | | w^2+17w+16=0 | | 3x+5+x=66 | | 0.20(x+10)+1.40x=66 | | 0.5(8w-6)=17 | | 5(-1.2)-y=4 | | 8w+3=6 | | 3*l=5 | | 4x-6+x=54 | | 5y+1+3y=-5 | | 4=16t-16t^2 | | 9-33=-4z | | -3x-4z=17 | | 5z^2-3x-2=0 | | 3(w-2)=6 | | 2x+3+x=54 | | w-3w=32 | | 2x+3=54 | | 0=-3x^2+2x+5 | | 4x-2(x+5)=-(2x+15) | | 4x-2(x+5)=-(2v+15) | | 3a+b=10 | | 3a-2b=-2 | | .75-9p=.60 | | 7x+9=3x-15 | | logx+log(x+15)=12 |

Equations solver categories